Pendidikan Kesehatan tentang Waspada 10 Titik Lengah Penyebaran Covid-19 - Diana Rachmania; Dina Zakiyyatul Fuadah (STIKES dan AKZI Karya Husada Kediri, 2022)
Corona Virus Disease or commonly referred to as Covid-19 is a disease that attacks the respiratory system, can cause several disturbances to the functions of the human body, and can spread quickly. Many people, especially students, are not aware of the 10 midpoints for the spread of Covid-19. Health education is needed to increase students' knowledge to prevent the spread of the Covid-19 virus. The purpose of this community service activity is to increase students' knowledge about vigilance against 10 midpoints for the spread of COVID-19. This activity was carried out on April 4-26, 2022 by empowering one of the students as a Kader in Health education activities. Furthermore, the delivery of material by selected person is given to students who are PMR members students at MTsN 8 Kediri as many as 30 students as activity participants. The method used in providing health education was lectures method and discussions conducted online (due to the Covid-19 pandemic) using pamphlets and materials in the form of power points. The measuring tool for assessing participants' knowledge was using a questionnaire in the form of a google form. The results of this activity were that as many as 53% of participants initially did not know the 10 midpoints for the spread of Covid-19 as shown from the results of the pre-test activity using a questionnaire. After the health education was carried out, the post-test results showed as many as 83% of the participants knew the 10 midpoints for the spread of Covid-19. Health education carried out by the service team was able to increase students' knowledge of being aware of 10 midpoints for the spread of Covid-19. It was hoped that students and the public will remain alert to the 10 midpoints of the spread of Covid-19 as an effort to prevent the spread of Covid-19.